A knowledge test on pressure injury in adult intensive care patients: Development, validation, and item analysis. Issue 4 (November 2022) - Botterman, Laurien; De Cock, Irene; Blot, Stijn I.; Labeau, Sonia O.
Abstract: Background: Pressure injuries are a major problem in critically ill patients, but both students' and intensive care nurses' knowledge about these injuries leaves room for improvement. As no knowledge test is currently available that focuses on pressure injuries in adult intensive care patients, we aimed to develop such tool, establish the content validity, and perform item analysis using Classical test theory. Methods: Test development followed established multiple-choice question-writing guidelines. Content validation used a Delphi procedure including eight international experts. Item analysis (question difficulty and discrimination power, and quality of the distractors) was based on the test results of a convenience sample who completed the test online, based on ready knowledge. Results: Four Delphi validation rounds resulted in a 24-item multiple-choice test within seven categories: Epidemiology, Aetiology, Prevention, Classification, Risk factors and risk assessment, Wound care, and Skin care. The content validity index was 0.96. The median score of 12 students and 38 qualified nurses was 12.5/24 (interquartile range 11–14.25; range 4–17; 52%). Least correct answers were in the categories Classification and Wound care. Item analysis revealed several knowledge gaps and misconceptions. Conclusions: The test has excellent content validity. The sample's overall score was low. Item analysis identified various training needs. Future users are recommended to further validate the test and establish its reliability, and to tailor it to their individual context and evaluation requirements. Highlights: A knowledge test was developed about pressure injury in critically ill patients. It is based on the most recent pressure injury clinical practice guideline. It was developed and validated using rigorous methodology. It can be adapted to future users' specific assessment needs.